Prevention and settlement of trade disputes in private sectors in Malaysia / Mohd. Farid Omar - Omar, Mohd. Farid (Faculty of Law, 1988)
Industrial law has been the subject of as a rapid transformation as can have happened to any legal subject in recent times, and is certainly one of the most difficult areas of law in which to keep up to date. In some ways it is a curious mixture of ancient and modem, for much old laws lie behind or at the base of new statutory law, and in some cases the old law continues to exist alongside the new. Much of the industrial relations system is rooted in the past. A brief knowledge of its history and its development is indispensible for an understanding of the present situation.